(RETRACTED) MENIMBANG DAKWAH DALAM KUBUR SEBAGAI DAKWAH INOVATIF DI ERA MILENIAL - Lukman Al Farisi (Jurnal Dakwah Tabligh, 2020)
This article tries to analyze the phenomenon of da'wah in the grave carried out by several religious leaders in the last five years. Da'wah which had been predicted as one of the innovative da'wah, is now no longer seen done by some of the perpetrators. So preaching with a model like this needs to be reconsidered. For this reason, this paper outlines whether this propaganda is still innovative at this time, especially in millennial circles. To find this out, the authors use Rogers' perspective on innovation. This perspective will look in more detail, whether propaganda in this way is an innovative propaganda. How if applied to millennial today, and how then Islam views an innovation. These issues are described in the discussions in this article, to answer some of the questions that arise, to later be a reflection of the missionary journey in Indonesia.